APPLICATION OF THE SNOWBALL THROWING TYPE OF COOPERATIVE LEARNING MODEL ON WATER POLLUTION MATERIAL AT AL-FURQAN JUNIOR HIGH SCHOOL - Hidayatullah; Oktafi Arinna Manasikkana (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2022)
In learning process, teachers was expect to be able to make students to be active, be able to solve problems, and learning to respect the opinions of other friends. One of the solutions to solve this problem is using the Snowball Throwing learning model. This study aims to determine the implementation of learning using the ‘snowball throwing’ model on water pollution material, the implementation of learning can be seen from student responses and student learning outcomes after implementing the snowball throwing learning model. The design of this study was a quasi-experimental using a one-group pretest-posttest research design. The population of this study was VII D class that consist of 23 students at SMP Al-Furqan Diwek Jombang. The sample used in this study was VII D class, with totaling 23 students. The data collection technique used in this study there are three methods, namely observation, test method, and questionnaire method. Based on the observations, the results of the implementation of learning using the Snowball Throwing model on teacher’s activities shows an average of 89.95%, and student’s activities was obtained an average of 91.9%. From these two averages, it can be seen that the implementation of learning went well. Student learning outcomes on cognitive tests have an average of 85% with complete criteria. While the student response has an average of 90.8% a positive response from students.